Towards Inflation Targeting in Sri Lanka - Ding, Ding (IMF Working Papers; Working Paper ;, 2011)
This paper develops a practical model-based forecasting and policy analysis system (FPAS) to support a transition to an inflation forecast targeting regime in Sri Lanka. The FPAS model provides a relatively good forecast for inflation and a framework to evaluate policy trade-offs. The model simulations suggest that an open-economy inflation targeting rule can reduce macroeconomic volatility and anchor inflationary expectations given the size and type of shocks faced by the economy. Sri Lanka could aim to target a broad inflation range initially due to its susceptibility supply-side shocks while enhancing exchange rate flexibility and strengthening the effectiveness of monetary policy in the transition to an inflation forecast targeting regime.